Methodology of Making Small Sculptures Based on Ceramics: Theoretical and Practical Approaches (International Journal of Scientific Trends, 2025)
This article describes the process of making small-sized figurines from ceramic clay in stages, and its methodological foundations are analyzed based on a scientific and practical approach. During the research, the materials, techniques, tools used in creating figurines and their interrelationships were studied in depth. The processes of clay selection, shaping, detailing, drying, baking, glazing and painting were considered in technological sequence, and the problems that arise at each stage and ways to overcome them were proposed. The pedagogical, artistic, aesthetic and cultural significance of the methodology for making small figurines was also analyzed, and its role in educating young artists, forming aesthetic taste and developing national artistic traditions was highlighted. The article used the methods of theoretical analysis, observation, comparison and practical testing. Based on the results obtained, methodological recommendations were developed, and the educational and practical potential of the art of making small figurines was highlighted.